Detection of serum HER2 in patients treated with neratinib or trastuzumab: analysis of the I-SPY Trial - Hensley, Mark; Lengfeld, Justin; Stoesz, Steven; Edwards, Michelle; Pass, Franklin; Hirst, Gillian L.; Brown-Swigart, Lamorna; van ‘t Veer, Laura; Esserman, Laura J.; Beckwith, Heather; Yee, Douglas (Frontiers in Oncology, 2025)
PurposeDrugs targeting human epidermal growth factor receptor 2 (HER2) have fundamentally changed the way breast cancer is treated. Measurement of HER2 expression has become increasingly important with the approval of therapies targeting a HER2-low population. Furthermore, predictive biomarkers for HER2 response would aid the clinical use of these drugs, and a blood-based assay of HER2 could provide important information for therapeutic options for patients.MethodsTo evaluate serum HER2 (sHER2) as a potential biomarker for breast cancer response, we examined the serum samples from patients treated with neratinib or trastuzumab combined with paclitaxel obtained from the I-SPY2 neoadjuvant trial. This trial included both HER2-positive and HER2-negative/low tumors.ResultsOf the patients with HER2-negative tumors, 26% had elevated sHER2, while 56% of the HER2-positive patients had elevated sHER2. The sHER2 levels declined with neoadjuvant therapy, and most patients had a clinical response to therapy. However, the sHER2 decline was not predictive of pathologic complete response.ConclusionsHER2 was detected in patients with HER2 tissue-positive and tissue-negative tumors. Further study will be needed to determine whether sHER2 is associated with patients with tumors that are HER2-low or ultralow and whether changes in sHER2 over time could predict response to HER2-targeted drugs.Clinical Trial Registrationclinicaltrails.gov, identifier NCT01042379.